‘Capabilities-friendly’ assessment for quality learning - Walker, Melanie; Nguyen, Tham (South African Journal of Higher Education, 2016)
Bridging the literatures of human capabilities and sustainable assessment for lifelong learning, this article explores the extent to which assessment practices can contribute to student learning and foster key capabilities for inclusive and sustainable lifelong learning. Social justice is understood here as expanding both student opportunities for individual well-being, but also the formation of agency commitments to advance the common good. The article therefore expands on a sustainable assessment approach to encompass preparing students for a fuller range of meaningful educational and social development goals. The papers draws on illustrative empirical data from the UK and then makes the case for the potential of a capabilities-friendly approaches to assessment to support the quality of learning in South African universities as a matter of urgency in the light of shockingly poor undergraduate completion rates.